Influenza A Virus Polymerase: Structural Insights into Replication and Host Adaptation Mechanisms - Boivin, Stéphane (American Society for Biochemistry and Molecular Biology, 2010)
The heterotrimeric RNA-dependent RNA polymerase of influenza viruses catalyzes RNA replication and transcription activities in infected cell nuclei. The nucleotide polymerization activity is common to both replication and transcription processes, with an additional cap-snatching function being employed during transcription to steal short 5′-capped RNA primers from host mRNAs. Cap-binding, endonuclease, and polymerase activities have long been studied biochemically, but structural studies on the polymerase and its subunits have been hindered by difficulties in producing sufficient quantities of material. Recently, because of heightened effort and advances in expression and crystallization technologies, a series of high resolution structures of individual domains have been determined. These shed light on intrinsic activities of the polymerase, including cap snatching, subunit association, and nucleocytoplasmic transport, and open up the possibility of structure-guided development of new polymerase inhibitors. Furthermore, the activity of influenza polymerase is highly host- and cell type-specific, being dependent on the identity of a few key amino acid positions in the different subunits, especially in the C-terminal region of PB2. New structures demonstrate the surface exposure of these residues, consistent with ideas that they might modulate interactions with host-specific factors that enhance or restrict activity. Recent proteomic and genome-wide interactome and RNA interference screens have suggested the identities of some of these potential regulators of polymerase function.